The Impact of Visual Impairment on Completion of Cognitive Screening Assessments: A Post-Hoc Analysis from the IVIS Study. Issue 1 (30th June 2022) - Bould, James; Hepworth, Lauren; Howard, Claire; Currie, Jim; Rowe, Fiona
Aim: The aim of this study was to evaluate completed cognitive screens in stroke survivors with and without visual impairment to explore whether the presence of visual impairment impacts on completion of cognitive screening. Materials and methods: Cognitive screening assessment was undertaken using the Oxford Cognitive Screen (OCS). Data from visual function assessments (inclusive of visual acuity, visual fields, eye movements and visual perception evaluation) were analysed to determine whether presence and/or type of visual impairment impacted on cognitive screening scores achieved. Covariates, including glasses use, gender, age at stroke onset and stroke type, were used to assess confounding impacts on scores attained during cognitive screening. Results: 1500 stroke admissions were recruited. One hundred ninety-seven who completed the OCS, were identified from the IVIS study database. Those who reported visual symptoms performed worse statistically on all cognitive tasks except the recall recognition (p = 0.232) and executive tasks (p = 0.967). Visual symptoms did not prevent participants from completing every section of the OCS (p = 0.095). In certain tasks, those not wearing their required glasses performed worse, including the executive function (p = 0.012), broken hearts and sentence reading tasks. Conclusions: Many tasks within cognitive screening assessment are impacted by presence of visual deficits, and adjustments, where possible (e.g. good lighting, large print) should be used to facilitate completion of cognitive screening. It is important to ensure required reading correction is worn during screening.